Physical status and motor performance of junior high school children age of 12-15 years in rural and urban Bantul Yogyakarta - Hastuti, Janatin (Universitas Gadjah Mada, 2007)
Background: Physical status and motor performance are influenced by living conditions. Those parametersare believed as factors indicated socioeconomics level of a population which effect on the children growth.Growth is also affected by other factors such as nutrition, genetics, hormone, disease, physical activity,environmental stress, and lifestyle. During growth, children adapt to their environment to achieve optimalfunctional efficiency.Objective: The aim of this research is to investigate physical status and motor performance of junior highschool children age of 12-15 years in Bantul Regency Yogyakarta Province, whether it is differ betweenrural and urban and between boys and girls.Methods: The research was done on 481 junior high school students of 12-15 years old, boys and girls,which consisted of 247 children living in District of Kretek (rural area) and 234 children living in Districtof Bantul (urban area). All subjects were measured on weight, height, upper arm girth, and skinfoldthickness of triceps. Physical status was determined from height, weight, body mass index, and musclearea of upper arm. Motor performance was measured on grip strength (left and right), jumping (standinglong jump method), throwing, and running tasks. Statistical analyses of chi-square, Pearson correlation,and linear regression were performed on data of physical status and motor performance of the children.Results: The results indicate that boys in both areas up to 14 years were lighter than the girls, but heavierat age of 15. However, boys were taller than the girls in all ages instead of rural boys at age of 12-13years. Body mass index and muscle area of upper arm of girls in both areas were greater than of boysexcept urban boys at age of 15 years. Boys appeared better in all motor performance tasks than the girlsas well as in motor performance relative to weight and height. Differences between rural and urban showthat urban children were taller and heavier than those were in rural. Body mass index and muscle area ofupper arms were greater in urban children. Children in urban area were also stronger in grip strength (leftand right). However, rural children were farther in jumping and throwing, and faster in running task..Conclusions: In conclusions, urban children were better in physical status and grips strength, while ruralchildren were better in jumping, throwing, and running performances. Instead of grips strength, motorperformances relative to weight and height of rural children were better than those of urban. Boys havebetter motor performance and motor performance relative to weight and height than girls.Key words: physical status; motor performance; rural and urban children.